2007
DOI: 10.1103/physrevlett.99.236404
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Phase Transition in the Two-Band Hubbard Model

Abstract: The interaction between itinerant and Mott localized electronic states in strongly correlated materials is studied within dynamical mean field theory in combination with the numerical renormalization group method. A novel nonmagnetic zero temperature quantum phase transition is found in the bad-metallic orbital-selective Mott phase of the two-band Hubbard model, for values of the Hund's exchange which are relevant to typical transition metal oxides. DOI: 10.1103/PhysRevLett.99.236404 PACS numbers: 71.27.+a, 7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 38 publications
4
55
0
Order By: Relevance
“…We have shown that this new transition is driven by an apparently new class of impurity-model phase transitions which should be classified and explored. The interplay with lattice-driven crystal field splittings and the orbitally selective Mott transition [14,15] is an open and interesting question. More generally the implications of the rich structure of the Slater-Kanamori interactions for the properties of the strongly correlated metal phase deserve further investigation.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations
“…We have shown that this new transition is driven by an apparently new class of impurity-model phase transitions which should be classified and explored. The interplay with lattice-driven crystal field splittings and the orbitally selective Mott transition [14,15] is an open and interesting question. More generally the implications of the rich structure of the Slater-Kanamori interactions for the properties of the strongly correlated metal phase deserve further investigation.…”
Section: )mentioning
confidence: 99%
“…We show that for densities per site n = 2, 3 the Mott transition occurs within or at the boundary of the frozen moment phase. As Costi and Liebsch have noted in the context of an orbitally selective Mott system, the presence of frozen moments may be expected to influence the Mott transition [15].The new phase appears for multiple orbitals, a different number of electrons than orbitals and a rotationally invariant on-site exchange U/3 > J > 0. While this situation is relevant to many compounds, it has has only recently become amenable to systematic study following the development of improved exact diagonalization [16] and efficient Monte Carlo methods [17,18].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…11 Finally, the possibility of so-called orbital-selective Mott transitions in multiband systems has been discussed extensively in the literature. 7,[12][13][14][15][16] These different trends underline the remarkably rich physics of Mott transitions in multiorbital materials.…”
Section: Introductionmentioning
confidence: 99%